PERLINDUNGAN HUKUM TERHADAP DEBITUR WANPRESTASI ATAS TAGIHAN YANG DILAKUKAN OLEH KREDITUR DALAM UTANG PIUTANG OLINE - Shofiyullah, Mukhammad Dzulkarnain (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Debtors are subjects who have legal responsibility to pay debts to creditors based on certain agreements or transactions, especially in the context of finance and civil law. This could be an individual, company or other entity that obtained a loan or credit facility. The agreement between the two includes the amount owed, interest rates, terms of payment, and the rights and obligations of each. If the debt is not fulfilled, the problem resolution process also plays an important role, where creditors can use legal steps and mechanisms such as debt restructuring or negotiations. A deep understanding of the rights and obligations of debtors is important to maintain a fair and sustainable relationship between creditors and debtors. Legal protection is an important principle in the legal system to ensure that individual rights are recognized and protected. This concept is rooted in human rights, promotes equality and fairness in legal norms. Its practical implications include the right of innocence in criminal law, contractual protection in civil law, and fair access to justice regardless of individual background. The global digital era is giving rise to new challenges such as online privacy and data protection. Legal protection is the main basis for a strong legal system, maintaining justice in various aspects of life.